Equilibrium bidding in the Eurosystem's open market operations - Ulrich Bindseil (European Central Bank (ECB), 2002)
Open market operations play a key role in allocating central bank funds to the banking system and thereby to steer short-term interest rates in line with the stance of monetary policy. This note presents some elements of a theory of bidding in central bank tenders in a framework such as the one of the Eurosystem. The ECB has so far used fixed rate tenders and a variant of the variable rate tender, which may be similar to a fixed rate tender depending on market circumstances. In doing so, it faced consecutively an 'under-' and an 'overbidding' issue. The tools developed in this note to understand the bidding behavior of banks in these operations allow revisiting these phenomena and the more general question of the optimal tender procedure and allotment policy.
Keywords: D84; E43; E52; 330; central bank liquidity management; Open market operations; tender procedures